Zayd Mutee Dammaj’s Short Story "A Woman" and the Concept of the Gaze: a Critical and Contextual Reading - Al-Wadhaf1, Yahya Hassan; Manqoush, Riyad Abdurahman (Journal of Amran University, 2022)
This paper attempts to analyze a short story by Zayd Mutee Dammaj, a late Yemeni novelist and short story writer (1943-2000). The story is entitled "A woman", written originally in Arabic, but translated later into English by May Jayyusi and Christopher Tingly. Building on an eclectic theoretical frame work, the paper demonstrates how the concept of gaze is employed by the narrator to communicate masculine and feminine connotations. Reading this short story closely takes us back into the socio-cultural circumstances of the old Sana'a city of the 70s and 80s generation inhabiting the city, a reality-like picture is transposed to the reader where senses of contact such as sight, smell, taste and enjoyment are intermingled in this narrative line.